The Decline of Modesty in Social Media: An Aqidah Based Solution - Norafifah Binti Ab Hamid.; Nor Azlina Binti Abd Wahab; Siti Nurul Izza Hashim.; Mohd Sobri Ellias; Dr Muaz Hj Mohd Noor (RSIS International, 2026)
Indexed by WOS/SCOPUS/ERA